CITRA DIFABELITAS DALAM KARYA RATNA INDRASWARI IBRAHIM - susilo Mansurudin (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstract. Injustice has been part of life for different ability people, especially for diffabled women in many parts of Indonesia. A diffabled woman writer, Ratna Indraswari Ibrahim, refuses the assumptionand proves on strength and spirit of life in women and diffable people through her works. This studydiscusses Ibrahim’s short stories about women and the life of her diffabled characters. The data sources ofthe study are novelettes by Ratna Indraswari Ibrahim. The data are quotes from the works that talk aboutdiffability. The study was based on understanding and interpretation processes. The study found that theIbrahim’s works discusses the image and strength of the diffabled woman character in defending for herrights. Ibrahim also proves that being diffabled does not necessarily mean constant mercy-seeking anddependence on others. Ibrahim tries to introduce a new paradigm that the diffabled people have the samepontential as the normal people do. The image of diffability is illustrated in her works that are fullyloaded with struggle of both a woman and a diffabled person.Kata kunci: citra, difabel, Ratna Indraswari Ibrahim